The Interplay between Zinc, Vitamin D and, IL-17 in Patients with Chronic Hepatitis C Liver Disease - Randa Reda; Amal A. Abbas; Mai Mohammed; Shahira F. El Fedawy; Hala Ghareeb; Rania H. El Kabarity; Rania A. Abo-Shady; Doaa Zakaria (Journal of Immunology Research)
Objectives. To assess zinc (Zn) and vitamin D (Vit. D) status in chronic Hepatitis C virus- (HCV) infected patients and their relationship to interleukin- (IL-) 17 and disease severity and then investigate whether Zn and Vit. D3 modulate IL-17 expression in chronic HCV patients. Methods. Seventy patients and fifty healthy subjects were investigated. Serum levels of Zn, Vit. D, and IL-17 were assessed in the patients group and subgroups. Patients lymphocytes were activated in vitro in the presence or absence of Zn or Vit. D3 and then intracellular IL-17 production was assessed using flow cytometry. Results. Zn and Vit. D were significantly decreased in HCV patients. Increasing disease severity leads to more reduction in Zn level opposed by increasing IL-17 level. Zn potently reduced IL-17 production in a dose-related fashion; however it did not exert any toxic effects. Although Vit. D apparently increases IL17 expression, it is unclear whether it is due to its toxic effect on cell count or lack of definite association between Vit. D and both IL-17 and disease severity. Conclusions. This study demonstrates that Zn modulates IL-17 expression and provides a rationale for evaluating this compound as a supplementary agent in the treatment of chronic HCV.